Method for designed and adaptation of complex organization and technical systems - Horbenko, Volodymyr; Korshetc, Olena; Korolyuk, Natalia; Nevgad, Sergey (Social Development and Security, 2020)
The results of the researches published in the article will be useful to specialists who study the problems of the organization and synthesis a complex organizational and technical systems (COTS) and their management. The article discusses the existing approaches to determining the forms of applying and methods for completing tasks of the COTS in various industries (fields) of activity. The analysis of the mutual relations among the forms of applying and methods for completing tasks of the COTS with their levels, tasks and capabilities is carried out. The main dependencies between the forms of applying and the ways of completing the tasks of COTS are determined. A new methodological approach to the synthesis and formalization of the structure, the definition of forms of applying and ways for completing tasks of SOTS is proposed. Based on the analysis of existing views on the research topic, it was determined that the lack of a unified approach does not give a clear answer how the functioning conditions, volume of tasks, available capabilities of COTS and its elements affect the definition of the forms of applying and ways of completing tasks at different levels of the COTS structure in each specific industry (sphere) of activity. The published results indicate that the effectiveness of the COTS functioning will depend of the industry (sphere) of activity, the forms of its applying and methods of completing tasks, which, in turn, is the realization of the capabilities of the system and its elements of a certain level of structure. It is determined that the discrepancies in the capabilities of the COTS elements to perform a certain amount of tasks are the basis for justifying the direction to improvement (adaptation) of the COTS existing structure. Based on the proposed methodological approach, the directions of further research are defined: the creation of tasks system for COTS elements at all levels in various industries (fields) of its activity; the formation a single system for COTS forms of applying and all its elements, taking into account the tasks defined for each specific industry (sphere) of activity; study of the mutual relations between tasks, opportunities, forms of applying, the influence of internal and external factors, as interacting entities, with the aim of determining ways to complete tasks by the COTS elements of various levels.